Petits riens sophocléens : Antigone III: (v. 513, 517–521, 527–530, 577–581, 594–602, 611–619, 666–667, 696–698, 703–704, 728–730) - Liberman, Gauthier (Hyperboreus, 2023)
This is the third of ﬁve sets of text-critical, exegetical and sometimes metrical remarks on Antigone. These *Sophocleuncula are not only minute philological notes but they involve broader issues having a bearing on the interpretation and meaning of the drama as a whole. These remarks were composed with a view to drawing attention to a number of forgotten or unseen diﬃculties and to trying to address a number of seen but unsolved problems more eﬃcaciously. The text and meaning of not a few other passages from works of Sophocles or of other writers are also dealt with.